Synthetic patch infection after congenital diaphragmatic hernia repair: A case series - Sabrina J. Flohr; Sierra D. Land; Holly L. Hedrick; Natalie E. Rintoul; Sanjeev K. Swami; Dustin D. Flannery (Elsevier, 2023)
Large congenital diaphragmatic hernia (CDH) defects that cannot be closed primarily often require reinforced repair. Synthetic patch is a widely used method of prosthetic patch closure. Infections associated with synthetic patch repair are poorly understood. This case series reviews ten patients cared for at the Children's Hospital of Philadelphia from 1996 to 2022 who underwent neonatal CDH repair with a synthetic patch and were subsequently diagnosed with suspected or confirmed patch infection, and proposes definitions for suspected and confirmed CDH patch infection to inform both current clinical care as well as future research on outcomes after CDH repair.